2017
DOI: 10.1080/14616696.2016.1268705
|View full text |Cite
|
Sign up to set email alerts
|

Support for restrictive immigration policies in the European Union 2002–2013: the impact of economic strain and ethnic threat for vulnerable economic groups

Abstract: Testing propositions from ethnic competition theory, we examine contextual and individual determinants of support for restrictive immigration policies in 26 European Union member states between 2002 and 2013, a period characterized by enduring economic downturn. We hypothesize that natives in vulnerable economic positions, similar to many migrants, are more restrictive toward immigration, because they perceive more economic strain and more ethnic threat. We expect that natives are more restrictive in times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…First, our focus on a specific type of perceived threat contributes to the nascent subfield of investigating and sometimes comparing different types of perceived immigrant threat (Callens and Meuleman, 2017; Ceobanu, 2011; Heizmann, 2015; Stephan et al, 2005; Stephan and Stephan, 2000), restrictiveness toward immigration (Ben-Nun Bloom et al, 2015; Green, 2009; Heizmann, 2016), far-right party success (Halikiopoulou and Vlandas, 2020), and outgroup attitudes (Meuleman et al, 2019) rather than using broad and general composite indicators of immigration attitudes per se (Ceobanu and Escandell, 2010; Van Setten et al, 2017). The general lesson from this literature is that different types of threat indeed have divergent causes and consequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our focus on a specific type of perceived threat contributes to the nascent subfield of investigating and sometimes comparing different types of perceived immigrant threat (Callens and Meuleman, 2017; Ceobanu, 2011; Heizmann, 2015; Stephan et al, 2005; Stephan and Stephan, 2000), restrictiveness toward immigration (Ben-Nun Bloom et al, 2015; Green, 2009; Heizmann, 2016), far-right party success (Halikiopoulou and Vlandas, 2020), and outgroup attitudes (Meuleman et al, 2019) rather than using broad and general composite indicators of immigration attitudes per se (Ceobanu and Escandell, 2010; Van Setten et al, 2017). The general lesson from this literature is that different types of threat indeed have divergent causes and consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we investigate whether perceived immigrant threat relates to short-term changes or long-term circumstances by modeling dynamic changes in the country’s economic and financial situation. Whereas many previous studies in this field used cross-sectional data, longitudinal designs are scarce (Bobo, 1983; Meuleman et al, 2009, 2018; Semyonov et al, 2006; Van Setten et al, 2017; Wright, 2011). This appears to mirror the general state of affairs in quantitative-comparative sociology (Giesselmann and Schmidt-Catran, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solidarity is a choice reflecting the individuals' socio-economic situation and the related cost-benefit calculations. We should thus expect that solidarity is more diffused among the most vulnerable and invulnerable social strata of the population (van Setten et al, 2017), as it implies more gains than losses for both sides. Recipients might suffer stigmatisation, once they disclose their neediness, but they gain financial help, while donors have to share their financial resources, but gain social recognition.…”
Section: Analytical and Explanatory Matters: Multi-layered Solidaritymentioning
confidence: 99%
“…Unemployed people are personally confronted with competition in their attempts to re-enter the labor market. Findings on the relation between unemployment and ethnic exclusionism are contradictory; some studies supporting that unemployed people perceive more ethnic threat and are more antiimmigrant than those in employment (Billiet et al, 2014;Scheepers et al, 2002;Schneider, 2008;Van Setten et al, 2017), and others finding no such relation (Citrin et al, 1997;Kuntz et al, 2017;O'Rourke and Sinnott, 2006). Heizmann (2015) found that unemployment has a stronger negative relation with perceived labor market competition when policies make it more difficult to re-enter the labor market, specifically when there is stronger employment protection legislation.…”
Section: Previous Researchmentioning
confidence: 99%